1994
DOI: 10.1002/pssa.2211450213
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film Nanoprocessing by Laser/STM Combination

Abstract: A new technique of laser direct writing of nanoscale structures is proposed. The technique is based on a local intensity enhancement of optical radiation near a tip of a scanning tunneling microscope and allows to overcome the fundamental spot limitation (about a half of the wavelength λ) of the conventional lens‐focused beams. In the first experimental results unconventional tips of silver are used in order to increase the effect. By using a laser with λ = 800 nm features of 10 to 40 nm in diameter are revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…In addition to the six hillocks already apparent in (a) a further hillock with a diameter of around 20 nm and a height of 5 nm appeared on the left side. This observation is similar to earlier studies [2][3][4] and will not be discussed further. We focus on dynamic measurements in the following.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In addition to the six hillocks already apparent in (a) a further hillock with a diameter of around 20 nm and a height of 5 nm appeared on the left side. This observation is similar to earlier studies [2][3][4] and will not be discussed further. We focus on dynamic measurements in the following.…”
Section: Resultssupporting
confidence: 91%
“…Whereas the possible use of forces or electric fields is already known from different applications [1] another quite new idea is the external injection of laser radiation into the tip-substrate gap. It has been shown that by using this technique nanostructures of different forms can be produced [2][3][4][5][6]. Even reliable single-atom deposition is achievable [5].…”
Section: Pacs: 6116p; 6570; 4260kmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, it was theoretically established that the field enhancement effect must be driven by an external field polarized along the axis of the pointed probe Martin and Girard, 1997;Furukawa and Kawata, 1998). Interestingly, the field enhancement was also studied in the context of STM as it was believed to mediate the transfer of atoms from the tip to the sample (Jersch and Dickman, 1996;Gorbunov and Pompe, 1994;Bragas, 1998). Raman scattering image of the same sample area recorded by integrating, for each image pixel, the photon counts that fall into a narrow spectral bandwidth centered around ν = 2615 cm 2 (indicated by the yellow stripe in c).…”
Section: Near-field Scattering and Field Enhancementmentioning
confidence: 99%
“…One approach in this respect consisted of the illumination of the tip of a scanning tunnelling microscope (STM) with a pulsed laser. Structures with lateral dimensions below 30 nm and therefore well below λ/2 could be produced underneath the tip [ 1,2]. It was proposed that the strong enhancement of the electromagnetic field in the vicinity of a tip, suggested e. g. by the calculations in [3], is responsible for this.…”
Section: Introductionmentioning
confidence: 99%